Recent advancements in chemical looping water splitting for the production of hydrogen. Issue 100 (14th October 2016) - Voitic, G.; Hacker, V.
Abstract : The extensive research in the field of chemical looping water splitting has enabled remarkable leaps towards a successful integration the technology into a future hydrogen infrastructure. Abstract : Chemical looping water splitting or chemical looping hydrogen is a very promising technology for the production of hydrogen. In recent years extensive research has enabled remarkable leaps towards a successful integration of the chemical looping technology into a future hydrogen infrastructure. Progress has been reported with iron based oxygen carriers for stable hydrogen production capacity over consecutive cycles without significant signs of degradation. The high stability improvements were achieved by adding alien metal oxides or by integrating the active component into a mineral structure which offers excellent resistance towards thermal stress. Prototype systems from small μ-systems up to 50 kW have been operated with promising results. The chemical looping water splitting process was broadened in terms of its application area and utilization of feedstocks using a variety of renewable and fossil resources. The three-reactor system was clearly advantageous due to its flexibility, heat integration capabilities and possibility to produce separate pure streams of hydrogen, CO2 and N2 . However two-reactor and single fixed-bed reactor systems were successfully operated as well. This review aims to survey the recently presented literature in detail and systematically summarize the gathered data.